Determining factor in Mathematics Achievements of the Freshmen College Students in an Asian Country - Lagrimas, Juliet C. (JPAIR Institutional Research, 2018)
Mathematics Attitude Scale Instrument was designed to the measure attitude toward learning mathematics. Motivating students to learn has been a major issue for teachers; they find it difficult to make their students enthusiastic and interested to learn mathematics since it was viewed by many students as a difficult subject. In view of this, the determinants in mathematics achievement of the 105 freshmen college students were looked into. Descriptive design was utilized. Questionnaire and grade sheets were used to gather data which were interpreted using frequency counts and percentages, weighted mean, and chi-square. Findings showed that the level of determinants in terms of confidence in learning mathematics, motivation and teaching strategies in mathematics was high; the level of mathematics achievement was good; there was a significant relationship between the respondents’ mathematics achievement and the confidence and motivation in learning mathematics; while there was no significant relationship existed between the respondents’ mathematical achievements and strategies in teaching mathematics. This study concludes that the learners must be motivated either intrinsically or extrinsically. High-achieving students feel more positive about their problem-solving abilities.